MULTIDIMENSIONAL KOMITMEN ORGANISASIONAL SEBAGAI MEDIATOR DALAM HUBUNGAN KEPUASAN KERJA DAN KEINGINAN BERPINDAH KERJA - NURHIDAYATI NURHIDAYATI; PRIYO GUNADI (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2009)
Many researchers in behavioural organizational science found that multidimensional effectof commitment variables- effective commitment; continuance commitment and normativecommitment- have different influence to turnover intention. This research aims to investigateinfluence multidimensional effect of commitment to turn over intention and to analyzemultidimensional of commitment as mediator variables. Questionaires distribute amonglectures and nurses of Sultan Agung Fondation amounting 59 respondents. The result usingregression analysis find that all of multidimensional of commitment have no significance toturn over intention and discussed deeply in discussion session.Keywords : Multidimensional, Commitment, Organizational, Turnover Intention